AB0803 Obesity is Associated with Psoriatic Arthritis and Contributes to the Increased Use of Biologics. (9th June 2015) - Cetin, P.; Keser, M.; Solmaz, D.; Sen, G.; Zengin, B.; Sari, I.; Akkoc, N.; Onen, F.
Abstract : Background: An increased prevalence of obesity and metabolic syndrome (Mets) has been reported in psoriatic arthritis (PsA) as compared with the general population suggesting an association between the inflammation and atherosclerotic risk factors. Takayasu arteritis (TA) is a systemic inflammatory disease which affects mostly the aorta and its main branches. Increased atherosclerosis has also been reported in Takayasu patients. Objectives: In this study, we aimed to investigate the prevalances of obesity and Mets in patients with PsA and to compare the results with those in patients with TA. Methods: This cross-sectional study included patients with PsA and age matched control patients with TA who were followed in the Rheumatology out-patient clinic at Dokuz Eylul University. Patients with body mass index (BMI; kg/m 2 ) between 25.0 and 29.99 were classified as overweight and those with ≥30 as obese. The NCEP-ACT III criteria were used to identify subjects with MetS. Disease activity was assessed in patients with PsA using the Composite Psoriatic Disease Activity Index (CPDAI), BASDAI and DAS28. HAQ and DLQI were used for the health assessment and BASFI for the functional status. Results: There were 117 PsA patients (78 female; mean age: 47.2±12.0 years; disease duration: 8.0±8.4 years) who fulfilled the CASPAR criteria and 32 TA patients (29 female; mean age: 43.5±11.3 years; disease duration: 8.3±8.7 years) who fulfilled the ACR 1990 classification criteria for TA.The prevalence of obesity and overweight was found to be higher in PsA compared with TA (29.9% versus 18.8% and 40.2% versus 28.0%, respectively; p=0.03). The prevalence of MetS was 28.2% in PsA and 18.8% in TA (p0.05).In the further analysis of obese, overweight patients and patients with normal BMI, no differences were found regarding disease activity, functional status, health assessment, disease duration, and glucocorticoid and DMARD use (p0.05). However there was a higher frequency of biologic use in the obese and overweight patients compared with those with normal BMI (42.9% and 23.4%, respectively vs 11.4%, p0.05) Conclusions: This study demonstrates a higher prevalence of obesity in PsA compared with TA. The increased use of biologics in obese patients suggests the association of obesity with worse disease severity in PsA. Disclosure of Interest: None declared